PEMANFAATAN METODE ELIMINATION AND CHOISE EXPRESSING REALITY (ELECTRE) PADA PENERIMA PROGRAM INDONESIA PINTAR TINGKAT SEKOLAH DASAR - Agustin Setiyorini; Eri Haryanto (Informasi Interaktif, 2021)
The Smart Indonesia program is a refinement of the Poor Student Assistance program which is given in cash to school-age children (aged 6-21 years). In determining the priority of PIP recipients itself is still carried out subjectively. The purpose of this study is to design and build a decision support application that can make it easier for schools to determine the priorities of potential PIP recipients. In this study using the Waterfall method because the final result of the study is a product in the form of decision support software for determining potential PIP recipients. While the method used in decision support making is the method of Elimination and Choise Expressing Reality (Electre). The Electre method is a multi-criteria decision-making method based on each appropriate criterion. The criteria used are: Active Status of Students, Orphans , Parents 'Work, Parents' Income, Number of Dependents who are still in school, Persons with Disabilities, KIP Holders, KKS Holders, PKH holders, SKTM holders, victims of natural disasters. From the results of alpha testing using the Black Box Testing technique and beta testing, functionally the system built has been successful, acceptable, can produce output as expected and is good enough to meet eligibility for useKeywords: PIP; Electre Method; Decision Support System; Waterfall method.